Evaluation of Different Combinations of Medium Chain Fatty Acids and Monolaurin as a Dietary Additive for Nursery Pigs - L. L. Thomas; A. R. Hartman; J. C. Woodworth; M. D. Tokach; R. D. Goodband; S. S. Dritz; J. M. DeRouchey; D. M. McKilligan; A. M. Jones (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 360 pigs (DNA 400 × 200, initial body weight (BW) = 15.0 lb) were used in a 35-d growth trial to evaluate the effects of adding medium chain fatty acids (MCFA) and monolaurin blends to the diet on growth performance of nursery pigs. Monolaurin is a monoglyceride of C12 and is thought to have antibacterial and antiviral properties. Following arrival to the nursery research facility, pigs were randomized to pens (5 pigs per pen) and allowed a 4-d acclimation period. Thereafter, pens of pigs were blocked by BW and randomized to 1 of 6 dietary treatments (12 pens per treatment). Treatments consisted of a basal diet containing no MCFA (control), the control diet with 1.0% added MCFA (a blend of C6, C8, and C10, 1:1:1 ratio; Sigma Aldrich, St. Louis, MO), or a 1.0% inclusion of 4 different blends of MCFA, lactic acid, and monolaurin-based additives (Tech Mix, LLC, Stewart, MN). The 4 blends consisted of 50% C6, 20% lactic acid, and increasing amounts of monolaurin (0, 10, 20, and 30%) at the expense of C12 (30, 20, 10, and 0%). Treatment diets were formulated and manufactured in two dietary phases (d 0 to 14 and 14 to 35). During phase 1, pigs fed the 1.0% 1:1:1 MCFA blend had increased (P= 0.037) average daily gain (ADG) compared to the control group. Pigs fed the 1.0% 1:1:1 MCFA blend and the mean of the 4 varying blends of MCFA, lactic acid, and monolaurin had improved (P<0.021) feed-to-gain ratio (F/G) compared to pigs fed the control diet. During phase 2, average daily feed intake (ADFI) and subsequently ADG increased (P<0 .057) for pigs fed the 1.0% 1:1:1 MCFA blend compared to the control group. Overall, increased (P<0.034) ADFI and ADG resulted in 2.1 lb greater final BW (P= 0.014) for pigs fed the 1.0% 1:1:1 MCFA blend compared to the control group. There was no evidence for differences between the mean of the different blends of MCFA, lactic acid, and monolaurin and the control group. In summary, the addition of a 1.0% 1:1:1 MCFA blend resulted in improved ADG, ADFI, and F/G compared with pigs fed a control diet. Based on the results of this study, the MCFA, lactic acid, monolaurin blend product improved F/G during phase 1 with comparable growth performance to those pigs receiving no supplementation thereafter. Additional research is warranted to understand if a blend of MCFA, acidifiers, and monoglycerides can be created to achieve similar benefits in growth performance shown from the 1.0% 1:1:1 MCFA blend and provide a beneficial economic return.
Keywords: Medium chain fatty acids; monolaurin; nursery pigs